Methodological considerations in longitudinal morphometry of traumatic brain injury - Kim, Junghoon; Avants, Brian; Whyte, John; Gee, James (Frontiers in Human Neuroscience, 2013)
Traumatic brain injury (TBI) has recently been reconceptualized as a chronic, evolving disease process. This new view necessitates quantitative assessment of post-injury changes in brain structure that may allow more accurate monitoring and prediction of recovery. In particular, TBI is known to trigger neurodegenerative processes and therefore quantifying progression of diffuse atrophy over time is currently of utmost interest. However, there are various methodological issues inherent to longitudinal morphometry in TBI that researchers need to be aware of. In this paper, we first overview several of these methodological challenges: lesion evolution, neurosurgical procedures, power, bias, and nonlinearity. We then introduce a sensitive, reliable, and unbiased longitudinal multivariate analysis protocol that combines dimensionality reduction and region of interest approaches. This analysis pipeline is demonstrated using a small dataset consisting of four chronic TBI survivors.